Taxonomy of attacks on wireless sensor networks - Han, Song; Chang, Elizabeth; Gao, L.; Dillon, Tharam S. (Springer-Verlag, 2005)
Along with sensor networks popularly utilized in the practical applications, to design optimistic security mechanisms is becoming a big challenge within the wireless sensor networks. As a result, it is imperative to propose a taxonomy of attacks on wireless sensor networks, since good security mechanism should address the attacks on wireless sensor networks. This paper presents the first work of the taxonomy of attacks on wireless sensor networks in a systematic way. This will help researchers in the area of wireless sensor networks to better understand wireless sensor network security and design more optimistic security countermeasures for wireless sensor networks.